Concentrating solar power and desalination plants : engineering and economics of coupling multi-effect distillation and solar plants /: engineering and economics of coupling multi-effect distillation and solar plants. ([2015]) - Palenzuela, Patricia; Alarcón-Padilla, Diego-César; Zaragoza, Guillermo
No abstract available